Democracy and the quality of economic institutions: Theory and evidence - Tommy Krieger (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
We present a simple model, illustrating how democracy may improve the quality of the economic institutions. The model further suggests that institutional quality varies more across autocracies than across democracy and that the positive effect of democracies on economic institutional quality increases in people's human capital. Using a panel data set that covers 150 countries and the period from 1920 to 2019, and different measures of economic institutional quality, we show results from fixed effect and instrumental variable regressions that are in line with the predictions of our model.
Keywords: D73; H11; O43; P14; P48; 330; Democracy; Development; Economic Institutions; Human Capital; Political Economy; Political Transitions